2020
DOI: 10.1016/j.ijscr.2020.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Benign multi-cystic peritoneal mesothelioma of the porta hepatis

Abstract: Highlights Benign multi-cystic peritoneal mesothelioma (BMPM) is a rare neoplasm of mesothelioma cells. They appear as grape-like cystic structures with thin walls containing mucinous or gelatinous fluid. The etiology of BMPM is unclear. Risk factors include pelvic inflammatory disease, endometriosis, and previous abdominal surgeries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…It has been reported that surgical resection alone of BMPM leads to around 50% of recurrence. Addition of HIPEC is superior to surgical resection alone as the recurrence rate of the disease decreases to 0%-21% [ 11 , 16 - 17 ]. The surgeon and the institution should be trained, equipped, and planned to administer this therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that surgical resection alone of BMPM leads to around 50% of recurrence. Addition of HIPEC is superior to surgical resection alone as the recurrence rate of the disease decreases to 0%-21% [ 11 , 16 - 17 ]. The surgeon and the institution should be trained, equipped, and planned to administer this therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although BMPM is generally considered to be benign because no cellular or nuclear atypia is seen by histological examination,[ 1 2 ] the local recurrence rate has been reported to be high. [ 3 4 ] It was reported that the timing of recurrence of BMPM ranged from early to late (from 1 month to 36 years) after surgical treatment.…”
mentioning
confidence: 99%